E-marketing Strategy and its Effect on Revenue and Customer Loyalty - Eliyanti Agus Mokodompit; Bahtiar Efendi; Ervana Chyrinne; Robbikal Muntaha Meliala; Silvina Mayasari (Politeknik Ganesha Medan, 2023)
In the rapidly evolving digital era, businesses and organisations must adapt to technological changes and changing consumer behaviour. One important aspect in dealing with these changes is the use of e-marketing strategies. The purpose of this study is to analyse e-marketing strategies and their effect on revenue and customer loyalty. This research is a literature review that adopts a qualitative method approach, which means it will analyse and interpret data by relying on information and text from various sources. The study results show that electronic marketing, or e-marketing, is a key element in the marketing strategy of modern companies. It is supported by advances in information and communication technology that have changed the way businesses operate. E-marketing has a significant influence on a company's revenue by increasing visibility, attracting new customers, and retaining existing customers. In addition, this strategy can also strengthen customer loyalty and help companies make smarter decisions through data analysis.